Dual-Phase Cathodes for Metal-Supported Solid Oxide Fuel Cells: Processing, Performance, Durability. Issue 8 (30th April 2019) - Udomsilp, D.; Thaler, F.; Menzler, N. H.; Bischof, C.; de Haart, L. G. J.; Opitz, A. K.; Guillon, O.; Bram, M.
Abstract : Cathode processing is one of the main challenges in the manufacturing of metal-supported solid oxide fuel cells (MSCs). Cathode sintering in ambient air is not applicable to MSCs, as oxidation of the metal substrate and the metallic Ni of the anode damages the cell. A recently developed ex situ sintering procedure for the LSCF cathode in an argon atmosphere was shown to significantly improve cathode adherence. However, the stability of the sintered cathode layer posed a challenge during storage in ambient air. In the present work, adapting the ex situ sintering approach to LSC/GDC dual-phase cathodes not only enabled the ex situ sintering process to be applied to LSC-based cathodes, but also resulted in the superior stability of the cathode after sintering. Despite the hygroscopic properties of the partially decomposed perovskite, LSC/GDC dual-phase cathodes were shown to withstand more than 1 year of storage in ambient air without failure. Electrochemical single-cell measurements and post-test analysis confirmed the reversibility of phase transformations and the electrochemical activity of such dual-phase cathodes. Current densities of 1.30 A cm − ² at 750°C, 0.85 A cm − ² at 700°C, and 0.54 A cm − ² at 650°C were obtained at a cell voltage of 0.7 V.